Research progress on natural products of main horticultural plants in China - LIANG Jiaojiao; CHEN Yunyi; WANG Yue; CHEN Jiebiao; CAO Jinping; LI Xian; SUN Chongde (浙江大学学报. 农业与生命科学版, 2021)
Natural products are widely found in nature, and their unique chemical diversity endows them with a variety of biological activities related to human health. China is rich in horticultural plant resources, in which the natural products are worthy of in-depth study and utilization. This article mainly focused on the identifi-cation, separation and purification of natural products of main horticultural plants in China and their application in activity evaluation systems, and summarized the progress of related research and the advantages and disadvantages of various evaluation methods, aiming to deepen the utilization of horticultural plant natural products, improve the separation efficiency of active substances and complete the evaluation systems, and further promote the integration and development of horticultural plant natural products related industries in the future.